Potentiometric Determination of the Formation Constants of Complexes of 3,3´ ,2"-Triaminodipropylethylamine with Co(II), Ni(II), Zn(II) and Cd(II) - Keypour, Hassan; Dehdari, Masoud; Salehzadeh, Sadegh (Asian Journal of Chemistry, 2010)
The tripodal tetraamine ligand N(CH2)3NH22(CH2)2NH2 (ppe) has been investigated for the first time as asymmetrical tetraamine chelating agent for cobalt(II), nickel(II), copper(II), zinc(II) and cadmium(II). The protonation constants of this ligand and formation constants. of its complexes have been determined potentiometrically in 0.1 M KCl at 25ºC. The successive protonation constants (log Kn) are: 10.38,9.68,8.95 and 3.81 (n = 1-4). One complex has the formula M(ppe)2+ is common to the all five metal ions for which the formation constants log βML, M = Co, Ni, Cu, Zn, Cd are:, 9.26, 11.95,15.98,12.01 and 8.33 respectively. In additon to the simple complex; copper(II), cobalt(II) and zinc(II) also give hydroxo complexes, Copper(II) and nickel(II) give the mono protonated complexes and nickel(II) give the ML2 complex. The [Zn(ppe)](ClO4)2 and [Cd(ppe)Cl](ClO4) complexes were also isolated.